Linking words. - Ponce Rodríguez, Bryan Armando (2022)
This report focuses on explaining how the demonstrative class called "linking words" helps to the future teacher to have an idea of what their field of work will be like through experimentation, and also it offers a clear perception of the factors that are involved in teaching for an effective learning. In addition, within this report, the future teacher explains how the process of this demonstrative class was, detailing within the planning how these classes were developed, from classroom management to the methodology that was applied in order to achieve the objectives that were proposed using as based the task-based learning method. So, the purpose of this demonstrative class is not only to demonstrate the knowledge acquired from the subjects studied throughout the entire university stage, but also to analyze what the future teacher must improve, so that the teaching-learning process develops in an effective way.